Cardiovascular determinants of exercise capacity in people with type 2 diabetes. (25th November 2020) - Gulsin, G; Henson, J; Brady, E.M; Sargeant, J; Swarbrick, D.J; Athithan, L; Htike, Z.Z; Biglands, J.D; Kellman, P; Khunti, K; Webb, D; Davies, M.J; et al.
Abstract: Background: The determinants of exercise capacity in people with type 2 diabetes (T2D), a group at high risk of heart failure, are unknown. Purpose: To assess the relationship between subclinical cardiovascular dysfunction and peak VO2 in adults with T2D. Methods: We enrolled asymptomatic adults with T2D and no prevalent cardiovascular disease. Matched controls were recruited for comparison. Subjects underwent echocardiography, cardiopulmonary exercise testing and adenosine stress cardiac MRI. Multivariable linear regression analysis was undertaken to identify independent associations between measures of cardiovascular structure and function and peak VO2 (Figure 1). Results: 247 adults with T2D (age 52±12y, 55% males, A1c 7.4±1.1%) and 78 controls were included. Subjects with T2D had increased concentric LV remodelling (LV mass/volume 0.84±0.14 vs. 0.76±0.11g/mL, p<0.001), reduced global longitudinal strain (−16.4±2.4 vs. −17.4±1.9%, p<0.001), lower aortic distensibility (2.75 (1.74–4.03) vs. 4.92 (2.65–7.13) mmHg-1x10–3, p<0.001), reduced myocardial perfusion reserve (2.60±1.24 vs. 3.54±1.15, p<0.001), and lower peak VO2 (19.0±5.6 vs. 28.0±9.1mL/kg/min, p<0.001) than controls. In a model containing age, sex, ethnicity, smoking status and systolic blood pressure, aortic distensibility (β=−0.466, p=0.033), E/e' (β=−0.344, p=0.001) and myocardial perfusion reserve (β=0.903, p=0.005) were independently associated with peak VO2 in subjects with T2D (Table 1). Conclusions: In asymptomatic people with T2D, aortic stiffening, diastolic filling, and myocardial perfusion reserve are key determinants of peak VO2, independent of age, sex, ethnicity, smoking status, or blood pressure. Funding Acknowledgement: Type of funding source: Public Institution(s). Main funding source(s): National Institute for Health Research - Career Development Fellowship (G P McCann, CDF-2014-07-045). British Heart Foundation - Clinical Research Training Fellowship (G S Gulsin)